1998
DOI: 10.2307/3579957
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Suppressor Loci on Chromosomes 11 and 14 May Be Required for Radiation-Induced Neoplastic Transformation of HeLa × Skin Fibroblast Human Cell Hybrids

Abstract: We have previously reported a linkage between radiation-induced damage to a putative tumor suppressor locus on fibroblast chromosome 11 and the re-expression of tumorigenicity in a hybrid cell line (HeLa x human skin fibroblast) used to study neoplastic transformation. Further investigation into the molecular basis of radiation-induced neoplastic transformation of the hybrid cell, CGL1, indicates that loss of fibroblast chromosome 11 appears to be necessary but not sufficient for neoplastic transformation. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Previous findings imply that loss of the entire chromosome 14 is associated with tumorigenicity of certain tumor hybrids (Srivatsan et al, 1986;Mendonca et al, 1998Mendonca et al, , 2000, but the location of candidate genes on this chromosome is presently not clear. In recent years, genetic losses of chromosome 14 have often been reported from different human tumors, including NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings imply that loss of the entire chromosome 14 is associated with tumorigenicity of certain tumor hybrids (Srivatsan et al, 1986;Mendonca et al, 1998Mendonca et al, , 2000, but the location of candidate genes on this chromosome is presently not clear. In recent years, genetic losses of chromosome 14 have often been reported from different human tumors, including NPC.…”
Section: Discussionmentioning
confidence: 99%
“…However, after a standard dose of 7 Gy of gamma or X-rays, radiation-induced transformation frequency of 4 -8 ϫ 10 Ϫ4 (40 -80 times above the spontaneous transformation frequency) could be observed (Redpath et al, 1987;Sun et al, 1988;Mendonca et al, 1990Mendonca et al, , 1998b. Molecular genetic characterization of these radiation-induced, neoplastically transformed cell lines (gamma-induced mutants, or GIMs) also has shown that the reversion to a tumorigenic phenotype was strongly associated with the loss of a fibroblast chromosome 11 (Mendonca and Redpath, 1989;Mendonca et al, 1991Mendonca et al, , 1995Mendonca et al, , 1998a. These hybrids had lost a copy of fibroblast chromosome 11 while retaining an intact copy of fibroblast chromosome 11.…”
Section: Introductionmentioning
confidence: 99%
“…Ten micrograms of the genomic DNA from each cell line was digested with various restriction enzymes. The digested DNAs were separated on 0.8% agarose gels (SeaKem, FMC Bioproducts, Rockland, ME) and transferred onto nylon membranes and hybridized to random primed 32 P-labeled probes (Feinberg and Vogelstein, 1983) as described previously (Mendonca et al 1995(Mendonca et al , 1998a. Because of the presence of repeat DNA in the probe sequences, preannealing at 65°C with Cot-1 DNA was required to reduce background.…”
Section: Southern Blot Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations